Improved high solid anaerobic digestion of chicken manure by moderate in situ ammonia stripping and its relation to metabolic pathway. (February 2020) - Bi, Shaojie; Qiao, Wei; Xiong, Linpeng; Mahdy, Ahmed; Wandera, Simon M.; Yin, Dongmin; Dong, Renjie
Abstract: Anaerobic digestion is a promising technology for the treatment of chicken manure but its application has limitations due to the inhibition induced by high concentration of ammonium nitrogen. In this study, the methane yield and methanogenic pathway of high solid anaerobic digestion of chicken manure, and their response to total ammonium nitrogen (TAN) variations with and without ammonia stripping were investigated through 194 days' continuously fed experiment. The results obtained show a 20% reduction in the TAN and a 30% reduction of volatile fatty acids by a moderate in-situ ammonia stripping. Methane yield increased by 34% and the enhanced acetoclastic and hydrogenotrophic methanogenic activities were significant. Firmicutes, Bacteroidetes, and Cloacimonetes were dominant at a TAN range of 5.8–6.8 g/L. Methanosarcina sp. was the dominant archaea and its relative abundance increased with in-situ ammonia stripping. The shifts of methanogenic pathway with and without stripping was quantified by 2– 13 C stable isotope probing and was consistent with the microbial community's changes. The positive effects achieved by in-situ ammonia stripping set the foundation for its use in the anaerobic digestion process of nitrogen-rich and high solid materials during treatment management. Highlights: Moderate in situ stripping reduced TAN by 20% and VFAs by 30%. Stripping increased both methane yield and methanogenic activities. The microbial communities were identified by high throughout sequencing. The methanogenic pathway was quantified by 2– 13 C isotope probing.